Ruthenium-Catalyzed Direct N-Formylation of Lactams with Paraformaldehyde - Lee, Hoseong; Kang, Byungjun; Lee, Sang-Ick; Hong, Soon Hyeok (Synlett, 2015)
Catalytic N-formylation of lactams was conducted with paraformaldehyde using Shvo’s catalyst. Various lactams were smoothly converted into N-formylimides without the use of a stoichiometric activating reagent.
Keywords: N-formylation; lactams; ruthenium; paraformaldehyde; N-formylimide; homogeneous catalysis